Is dipyrone effective as a preemptive analgesic in third molar surgery? A pilot study - Favarini, Vinícius Tatsumoto; Lima, Carlos Alysson Aragão; da Silva, Rogério Almeida; Sato, Fábio Ricardo Loureiro [UNESP] (Springer Nature, 2018)
Purpose: Studies on preemptive analgesia in maxillofacial surgery have shown several controversial clinical results, mainly due to the absence of a methodological standard, besides a wide variety of studied drugs. This study intended to answer the following hypothesis: Is the administration of dipyrone preemptively capable of decreasing trans- and postoperative pain in the third molar surgical extraction? Methods: A pilot prospective double-blind placebo-controlled study was carried out with 25 patients submitted to the third molar surgical extraction at two moments, one side in each intervention. Dipyrone (1 g) was preemptively administered (study group) for the extraction of two third molars on the same side and, in a second surgical procedure, dipyrone (1 g) was administered in the immediate postoperative period (control group). Evaluated variables were the amount of anesthetic, pain perceived through the visual analogue scale (VAS) in transoperative and immediate postoperative periods, and over 12-h investigation period, analgesic consumption, duration of surgery, and time to rescue analgesia. Results: The results were submitted to Student’s t test and statistical differences were observed in transoperative (p < 0.05) and immediate postoperative (p < 0.01) periods, while the other studied variables did not present statistical differences. Conclusion: The preemptive administration of dipyrone decreased the perception of transoperative and immediate postoperative pain when compared to its use after surgery only.
Keywords: Dipyrone; Preemptive analgesia; Third molar surgery